Genitourinary syndrome of menopause – is the problem solved? State of the art 2018 - Szymański, Jacek; Zaręba, Kornelia; Jakiel, Grzegorz; Słabuszewska-Jóźwiak, Aneta (Menopause Review/Przegląd Menopauzalny, 2018)
Vulvovaginal atrophy accompanied by lower urinary tract dysfunction related to low levels of estrogen and androgens is labeled as genitourinary syndrome of menopause (GSM). Although this condition affects most postmenopausal women worldwide, it seems to be underdiagnosed and undertreated. Women should be properly advised to choose an adequate treatment modality to improve their quality of life, sexual relationships and social activity. The aim of this article to is increase knowledge of GSM. The current treatment options, both hormonal and non-hormonal, are reviewed. Topical estrogen therapy still remains the gold standard, but the demand for individually tailored therapy is growing. New treatment modalities are continuously included in clinical practice. They should consider the whole personality of a woman as well as cultural and social factors. Further studies on GSM and on the effectiveness of various treatment options are necessary to achieve this purpose.